A systematic method introduced a common lncRNA-miRNA-mRNA network in the different stages of prostate cancer - Vahabzadeh, Gelareh; Khalighfard, Solmaz; Alizadeh, Ali Mohammad; Yaghobinejad, Mahsa; Mardani, Mahta; Rastegar, Tayebeh; Barati, Mahmood; Roudbaraki, Morad; Esmati, Ebrahim; Babaei, Mohammad; Kazemian, Ali (Frontiers in Oncology, 2023)
Introduction The present study aimed to investigate the interaction of the common lncRNA-miRNA-mRNA network involved in signaling pathways in different stages of prostate cancer (PCa) by using bioinformatics and experimental methods. Methods Seventy subjects included sixty PCa patients in Local, Locally Advanced, Biochemical Relapse, Metastatic, and Benign stages, and ten healthy subjects were entered into the current study. The mRNAs with significant expression differences were first found using the GEO database. The candidate hub genes were then identified by analyzing Cytohubba and MCODE software. Cytoscape, GO Term, and KEGG software determined hub genes and critical pathways. The expression of candidate lncRNAs, miRNAs, and mRNAs was then assessed using Real-Time PCR and ELISA techniques. Results 4 lncRNAs, 5 miRNAs, and 15 common target genes were detected in PCa patients compared with the healthy group. Unlike the tumor suppressors, the expression levels of common onco-lncRNAs, oncomiRNAs, and oncogenes showed a considerable increase in patients with advanced stages; Biochemical Relapse and Metastatic, in comparison to the primary stages; Local and Locally Advanced. Additionally, their expression levels significantly increased with a higher Gleason score than a lower one. Conclusion Identifying a common lncRNA-miRNA-mRNA network associated with prostate cancer may be clinically valuable as potential predictive biomarkers. They can also serve as novel therapeutic targets for PCa patients.